Relation between third trimester urinary iodine concentrations and newborn thyrotrophic hormone - farahani, Heidar; Rezvanfar, Mohammad Reza; Rafiei, Mohammad; Salehi, Elaheh; Ebrahimi, Elham; Kazemi Majd, Rezvan (Archives of Medical Laboratory Sciences, 2019)
Background: The aim of the study was to evaluate the third trimester urinary iodine excretion and to assess its relation with newborns thyroid function. Materials and Methods: A total of 208 healthy third trimester pregnant women without previous history of thyroid disease were included in the study. Urinary iodine levels of mothers were measured and neonatal TSH levels were screened on the 3- 5th day following birth. Results: The median urinary iodine level in the mothers was 50μg/L. According to WHO criteria for iodine status:14.9%, 34.1% and 49.6% had severe, moderate and mild iodine deficiency, respectively, and only 1.4%, had the adequate iodine intake . In 6 neonate (2.8%) who their TSH level were between 5- 10 IU/ml, nobody had criteria for congenital hypothyroidism at recall visit (15th day). Our results showed the reverse relation between mean Neonatal TSH levels and mother’s third trimester iodine level (r= -0.19, p=0.006). Conclusion: Although all of mothers included in this study stated that they were using iodized salt, iodine deficiency was frequent . There was also a significant relation between mean neonatal TSH levels and mother’s third trimester iodine urinary level.